PENGARUH EKUITAS MEREK DAN SISTEM PEMBAYARAN BERBASIS QRIS TERHADAP KEPUTUSAN PEMBELIAN PADA FLOC.CO AND EATERY MEDAN - Siregar, Muhammad Ibrahim Hafizh; rafiki, ahmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the influence of brand equity and QRIS-based payment systems on purchasing decisions at FLOC.CO and Eatery in Medan. Brand equity is studied through the dimensions of brand awareness, brand association, perceived quality, and brand loyalty. The QRIS-based payment system is identified as a factor that can influence purchasing decisions in the food and beverage business context. The research method used is a survey with data collection through questionnaires distributed to consumers who have shopped at FLOC.CO and Eatery. This research is a quantitative descriptive study. Therefore, the author will use statistical data processing to obtain accurate or definite results that can be systematically explained. The sample in this study is 66 people. The technique used for sampling in this study is accidental sampling. The obtained data were analyzed with statistical acquisitions using multiple linear regression analysis and partial regression tests managed using the SPSS V.20 program, 2024. The results of the data management show that Brand Equity and QRIS-based Payment Method have a contribution to the Purchase Decision. This is indicated by the regression test results showing that the regression coefficient value is positive with a value of b = 0.736. This means that if there is an increase in the value of variable X1 by one point, it will influence the purchase decision value by 0.736, assuming that other independent variables have a value of 0 or constant, and Brand Equity has contributed to influencing the purchase decision by 7.3%. Meanwhile, the QRIS-based Payment System regression test shows that the regression coefficient value is positive with a value of b = 0.249. This means that if there is an increase in the value of variable X2 by one point, it will influence the purchase decision value by 0.249, assuming that other independent variables have a value of 0 or constant, and the QRIS-based Payment System has contributed to influencing the purchase decision by 2.4%. Moreover, the t-value (16.220) > t-table (1.997) and Sig (0.000) < 0.05. Thus, it can be concluded that the hypothesis is rejected, and the alternative hypothesis is accepted, meaning that Brand Equity has a partial positive and significant effect on the purchasing decision of FLOC.CO and Eatery. And for the QRIS-based Payment System, it has a t-value (5.200) > t-table (1.997) and Sig (0.000) > 0.05. Therefore, it can be concluded that the hypothesis is rejected, and the alternative hypothesis is accepted, meaning that the QRIS-based Payment System has a partial positive and significant effect on the purchasing decision of FLOC.CO and Eatery.